Pembelajaran Bilingual dan Usaha Sekolah Memaksimalkan Perkembangan Kognitif, Sosial, Dan Motorik Anak - Muhammad Khoiruzzadi; Nabillah Karimah (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2020)
This study aims to describe bilingual learning and school efforts in maximizing children's cognitive, social and motor development. This research is included in the field research with a descriptive qualitative approach. The data is taken from the results of observations of learning in happy classrooms, classroom teacher interviews and principals at Play group, Day Care and Kindergarten Ceria Demangan Yogyakarta. The results showed that bilingual learning is done both from warming up activities, circle time, breafing activity, snack time, free play, and going home. School effort in maximizing children's cognitive development is by the use of learning methods that are attractive to children. Children's social development by teaching children to work together, be responsible, be disciplined and help one another. Children's motor development with sports activities, social service, and learning while playing. And finally, complete play facilities are very supportive of children's cognitive, social and motor development.